PENGARUH STATUS SOSIAL EKONOMI KEPALA KELUARGA TERHADAP KEADAAN SANITASI LINGKUNGAN KELUARGA PADA MASYARAKAT BANTARAN SUNGAI DI DESA MUARA PENIMBUNG ULU - Bayu Pamungkas; Yoyok Hendarso; Zulfikri Suleman (Jurnal Media Sosiologi (JMS), 2021)
This study examined "The Influence of SocioEconomic Status of The Family Head on the State of Family Environmental Sanitation in the Bantaran Sungai Community in Muara Penimbung Ulu Village". This research is a kuantitaif research that is associative. Data collection techniques are carried out by disseminating questionnaires or questionnaires and taking documentation. The scale used in the questionnaire is the Guttman scale. The number of respondents in this study amounted to 81 respondents. Data analysis techniques with binary logistic regression formulas. The results showed that there is an influence of the socioeconomic status of the head of the family on the state of sanitation of the family environment in the riverbank community in the village of Muara Penimbung Ulu, indicated by the results of binary logistics regression test showed rhitung 0.002 < 0.05 rtabel and the amount of influence from the study of 0.187 or 18%.